(untitled) (Rivista italiana di Paleontologia e Stratigrafia, 2020)
A fine skull of a sirenian from Early Pliocene littoral sands with Late Ruscinian terrestrial mammals near Siena is referred to Metaxitherium gervaisi (Capellini, 1872); it provides detailed information on the characters of this species, which was originally based on more fragmentary material. Comparison with other species shows that sirenians of southern France and Italy represent a chronocline characterised by a progressive increase in size, from the Early Ruscinian M. serresi, the smallest species, through M. gervaisi to the large M. forestii, of Late Pliocene age. In southern Europe sirenians are not recorded after the end of the Pliocene,